An Analysis of Factors Influencing College Students’ Satisfaction With E-learning: A Case Study of Guangdong City Technician College in Guangdong, China - Meixiu, Jin (Scholar: Human Sciences, 2025)
Purpose: This study investigates the influence of six independent variables (System Quality Perceived Usefulness, Perceived Ease of Use, and Confirmation) on the dependent variable (Satisfaction) with e-learning. Additionally, it aims to identify significant differences between pre-and post-strategic planning interventions. Research design, data, and methodology: The research utilized the Index of Item-Objective Congruence (IOC) for validity and Cronbach’s Alpha in a pilot test (n=30) for reliability. Ninety valid responses from Guangdong City Technician College students were analyzed using multiple linear regression and ANOVA tests to verify the significant relationships between variables. Following this, a strategic planning intervention was implemented, and the same 90 students were surveyed post-intervention. Paired samples t-tests were conducted to compare pre-and post-intervention results. Results: The multiple linear regression analysis revealed that System Quality, Service Quality, Information Quality, Perceived Usefulness, Perceived Ease of Use, and Confirmation significantly impacted students’ satisfaction with e-learning. The paired samples t-test demonstrated significant differences in all variables between the pre-and post-strategic planning stages, indicating the effectiveness of the interventions. Conclusions: This research highlights the importance of strategic planning in enhancing e-learning satisfaction by improving system and service quality, information relevance, usability, and perceived usefulness. The findings underscore the need for continuous monitoring and iterative improvements to maintain high levels of student satisfaction in e-learning environments.